2002
DOI: 10.1002/zoo.10006
|View full text |Cite
|
Sign up to set email alerts
|

Use of levonorgestrel as an effective means of contraception in the white‐faced saki (Pithecia pithecia)

Abstract: This study examines the use levonorgestrel (Norplant ® -2) as a means of contracepting white-faced sakis (Pithecia pithecia). A 70-mg silastic tubule of levonorgestrel was implanted subdermally between the scapulae in four multiparous and two nulliparous females. Implants remained in the females housed with males of proven fertility for 81 to 734 days. All females experienced low, acyclic levels of estrone conjugates (E 1 C, < 500 ng/mg Cr) and pregnanediol-3-glucuronide (PdG, < 1.5 µg/mg Cr) after insertion o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 23 publications
1
13
0
Order By: Relevance
“…Subjects expressed aggression at peripheral individuals via chasing and provided details about social strategies that researchers should examine further in free-ranging sakis. I also present data on female reproduction and development that accord well with studies of captive sakis (Savage et al, 1992(Savage et al, , 2002Shideler et al, 1994).…”
supporting
confidence: 82%
See 2 more Smart Citations
“…Subjects expressed aggression at peripheral individuals via chasing and provided details about social strategies that researchers should examine further in free-ranging sakis. I also present data on female reproduction and development that accord well with studies of captive sakis (Savage et al, 1992(Savage et al, , 2002Shideler et al, 1994).…”
supporting
confidence: 82%
“…that could well extend to differences in grouping patterns and habitat use. Savage et al (1992Savage et al ( , 2002 defined reproductive parameters for captive white-faced saki females. A 17-d estrous cycle was documented in wild sakis and the 21-mo IBI Shideler et al (1994) documented for captive sakis identical to we calculated for the wild sakis (average of 21.2 mo, range 12-36 mo).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LNG has strong progestational effects and lacks estrogen-like activity [Lemus et al, 1992]. Although effective and efficient as a contraceptive, the mode of contraceptive action of LNG is multiple and varies from species to species [Croxatto et al, 1982;Shaaban et al, 1984Shaaban et al, , 1993Brache et al, 1985;Ratsula et al, 1989;Faundes et al, 1991;Telleria et al, 1994;Kuhnz et al, 1995;Shirley and Bundren, 1995;Bettinger et al, 1997;Savage et al, 1998;Tell et al, 1999]. The modes of action of LNG include anovulation, deficient luteal phases, suppression of follicular growth, and alterations to cervical mucus.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, ovulation in LNG treated koalas may be prevented, even if mating is achieved through inhibition of the LH surge, as is the case in many other spontaneous ovulating species including the tammar wallaby (Baldwin et al, 1994, Bettinger et al, 1997, Savage et al, 2002, Hynes et al, 2007. The ability of luteal or exogenous progestogen to suppress gonadotrophin secretion and subsequently inhibit follicular growth in the koala has not been specifically investigated, however, Johnston (1999) has shown that behavioural oestrous is at least suppressed during the luteal phase in both pregnant and non-pregnant koalas.…”
Section: Introductionmentioning
confidence: 99%